THE SCOPE OF CISG IN CHINA AND BRAZIL AND FACILITATION OF TRADE WITH PORTUGUESE SPEAKING COUNTRIES - Ramaswamy, M. (PEOPLE: International Journal of Social Sciences, 2017)
Trade facilitation achieved through harmonization of private law governing international trade is well recognized. The CISG, albeit being a hall mark of a successful harmonization attracted a limited interest from the Portuguese speaking (Lusophone) countries except Brazil. In the light of China’s trading interest with the Lusophone Countries, the question of relevance of the CISG to promote Sino-Lusophone trade gains significance. To address the above question, this paper seeks to examine the scope and limitations of the CISG application to China and Brazil and adopts a case law method to examine the jurisprudence resulting from judicial interpretations and arbitration awards. The paper examines the reception of the CISG in both countries, before enquiring the significance of the CISG in facilitating their bilateral trade. The paper briefly refers to the implications arising from the lack of formal extension of the CISG by China to Macau SAR, which has been designated as a jurisdiction to facilitate trade between China and Lusophone Countries. In conclusion, the paper underscores the importance of the CISG based on the findings of its scope of application in China and Brazil and calls for the need to study the phenomenon further in the light of the experience of post Brazilian accession to the CISG.